2019
DOI: 10.2478/intox-2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

The hepatoprotective and antioxidative effect of saffron stigma alcoholic extract against vincristine sulfate induced toxicity in rats

Abstract: Vincristine (VCR) is an important anti-cancer drug, which is highly toxic for the liver. This study aimed at evaluating the protective effect of alcoholic extract of saffron stigma against vincristine hepatotoxicity in the rat. A total number of 50 rats were randomly divided into 10 groups, including controls, rats receiving 0.25 mg/kg (A group), 0.5 mg/kg (B group), 0.75 mg/kg (C group) VCR, 0.25 mg/kg VCR + 0.5 mg/kg saffron (D group), 0.5 mg/kg VCR + 0.5 mg/kg saffron (E group), 0.75 mg/kg VCR + 0.5 mg/kg s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…(Singh et al, 2018), although not all results have always been positive, particularly in the case of vincristine. This increase in lipid peroxidation associated with liver toxicity (Harchegani et al, 2019) or peripheral neurotoxicity (Erdogan et al, 2020) caused by vincristine has been observed in treatments with cumulative doses of vincristine higher than those used in this study. Besides, it is important to mention that a slight but not significant increase in plasma levels of MDA was observed after two weeks of suspension of vincristine treatment.…”
Section: Discussionsupporting
confidence: 56%
“…(Singh et al, 2018), although not all results have always been positive, particularly in the case of vincristine. This increase in lipid peroxidation associated with liver toxicity (Harchegani et al, 2019) or peripheral neurotoxicity (Erdogan et al, 2020) caused by vincristine has been observed in treatments with cumulative doses of vincristine higher than those used in this study. Besides, it is important to mention that a slight but not significant increase in plasma levels of MDA was observed after two weeks of suspension of vincristine treatment.…”
Section: Discussionsupporting
confidence: 56%
“…30 The most wellestablished mechanism of how vincristine induces tumor cell death is that vincristine impairs the polymerization of mitotic spindle microtubules, causing cell division arrest in the metaphase and apoptosis in mitotic cells. 9,18 As reported previously, vincristine exerts antimitotic effects on both tumor and normal cells and causes both apoptosis and necrosis in normal hepatocytes. 9 Cell apoptosis may lead to structural changes in the cell lipid membrane, which are associated with lipid methylene vibrations.…”
Section: Sr-ftir Microspectroscopy Analysismentioning
confidence: 72%
“…9,18 As reported previously, vincristine exerts antimitotic effects on both tumor and normal cells and causes both apoptosis and necrosis in normal hepatocytes. 9 Cell apoptosis may lead to structural changes in the cell lipid membrane, which are associated with lipid methylene vibrations. 30,47 In the present study, increases in ν as (CH 2 )/ν as (CH 3 ) and ν s (CH 2 )/ν s (CH 3 ) indicated alterations in lipid structures and the presence of more longchain fatty acids in the vincristine-treated WRL68 cells.…”
Section: Sr-ftir Microspectroscopy Analysismentioning
confidence: 72%
“…32,33 Some studies showed that the anti-proliferative activity of crocin like vincristine involves targeting microtubules 10 and p53-dependent and -independent mechanisms in colon cancer cells. 11,12 Crocin triggers apoptosis by increasing the Bax/Bcl-2 ratio and caspase activation in human gastric adenocarcinoma without affecting human normal fibroblast skin cells. 34 Also, Luo et al reported that the combination of crocin with cisplatin exerts growth suppression and apoptosis in gastric carcinoma cells.…”
Section: Crocin Time-dependently Induced Apoptosis In Comentioning
confidence: 99%
“…9 Like vincristine, crocin's anti-proliferative activity involves targeting microtubules 10 or p53dependent and -independent mechanisms in cancer cells. 11,12 In our laboratory, we observed that crocetin, a hydrolyzed form of crocin, exerts anti-proliferative, proapoptotic, and pro-differentiating impacts on human leukemia cells by inhibiting protein kinase B (Akt)mediated pro-survival cascades, raising the intracellular Bcl-2-like protein 4 (Bax)/Bcl-2 ratio, and reducing Tyrosyl-DNA phosphodiesterase 1 (TDP1) enzyme activity and the expressions of promyelocytic leukemiaretinoic acid receptor alpha (PML-RARα), Histone deacetylase 1 (HDAC1), and Multidrug resistance (MDR)-associated proteins. 13,14 Our laboratory has been interested in crocin's application in lymphoma and leukemia.…”
mentioning
confidence: 99%